Current Treatment of Comorbid Insomnia and Obstructive Sleep Apnea With CBTI and PAP-Therapy: A Systematic Review - Bahr, Katharina; Cámara, Rafael J. A.; Gouveris, Haralampos; Tuin, Inka (Frontiers in Neurology, 2018)
Insomnia and obstructive sleep apnea (OSA) are often both present in patients with sleep-disordered-breathing. The coexistence of the two disorders shows an increase in cumulative morbidity and an overall greater illness severity. There is still considerable controversy regarding management decisions in this group of patients. This systematic review focused on more recent evidence regarding treatment of patients presenting with both clinical entities of comorbid insomnia and obstructive sleep apnea in terms of their management, especially using combinations of positive airway pressure (PAP, namely aPAP, cPAP, adaptive servo-ventilation[ASV]) and CBTi as well as each one of these two modalities alone. As a conclusion it is necessary to specifically target distinct combinations of both insomnia (initial, middle, late) and OSA (mild, moderate, severe) phenotypes. The present review gives reason to assume that both CBTi and PAP-therapy are necessary. However, it appears that distinct treatment patterns may suit different COMISA phenotypes.